2004
DOI: 10.1002/ijc.20716
|View full text |Cite
|
Sign up to set email alerts
|

Dominant B cell epitope from NY‐ESO‐1 recognized by sera from a wide spectrum of cancer patients: Implications as a potential biomarker

Abstract: Monitoring the spontaneous antibody (Ab) response against a panel of relevant tumor-associated antigens (TAA) in cancer patients may provide useful information regarding the clinical status of cancer. However, current Ab detection approaches require the purification of recombinant proteins, which is often difficult to achieve. In order to bypass the purification of recombinant proteins, we identified a dominant B-cell epitope from a shared tumor antigen NY-ESO- In the last 10 years, molecular identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 21 publications
6
37
0
Order By: Relevance
“…We also analyzed the epitope specificity of anti-NY-ESO-1 antibodies in 12 sera from cancer patients (12 melanoma, 1 non small cell lung cancer, 1 breast cancer) using recombinant protein fragments of NY- and matrix-bound synthesized decamer peptides with 5 amino acid overlaps between every 2 consecutive decamer peptides covering the entire NY-ESO-1 molecule. Our results confirm the finding that most sera react with the epitope described by Zeng et al 1 However, our scanning of the entire NY-ESO-1 molecule irrespective of predicted hydrophilicity, surface accessibility and buried residues revealed that there is a second epitope against which IgG antibodies in 7 of the 12 anti-NY-ESO-1 antibodypositive sera were shown to react. This epitope is located between amino acids 96 and 125, with a core region to be assigned to p106-115 (Fig.…”
Section: Dear Sirsupporting
confidence: 91%
See 1 more Smart Citation
“…We also analyzed the epitope specificity of anti-NY-ESO-1 antibodies in 12 sera from cancer patients (12 melanoma, 1 non small cell lung cancer, 1 breast cancer) using recombinant protein fragments of NY- and matrix-bound synthesized decamer peptides with 5 amino acid overlaps between every 2 consecutive decamer peptides covering the entire NY-ESO-1 molecule. Our results confirm the finding that most sera react with the epitope described by Zeng et al 1 However, our scanning of the entire NY-ESO-1 molecule irrespective of predicted hydrophilicity, surface accessibility and buried residues revealed that there is a second epitope against which IgG antibodies in 7 of the 12 anti-NY-ESO-1 antibodypositive sera were shown to react. This epitope is located between amino acids 96 and 125, with a core region to be assigned to p106-115 (Fig.…”
Section: Dear Sirsupporting
confidence: 91%
“…
Dear Sir,We read with great interest the article by Zeng et al 1 Basing their study on predictions of hydrophilicity, surface accessibility and buried residues, they restricted their search for NY-ESO-1 B-cell epitopes to the first N-terminal 74 amino acids and identified a dominant B-cell epitope that resides in the first 40 amino acids of the NY-ESO-1 molecule, with amino acids 11-30 representing the core of this B-cell epitope. We also analyzed the epitope specificity of anti-NY-ESO-1 antibodies in 12 sera from cancer patients (12 melanoma, 1 non small cell lung cancer, 1 breast cancer) using recombinant protein fragments of NY- and matrix-bound synthesized decamer peptides with 5 amino acid overlaps between every 2 consecutive decamer peptides covering the entire NY-ESO-1 molecule.
…”
mentioning
confidence: 99%
“…While many studies show promising results, other studies illustrate significant limitations to the use of tumour antigens for cancer detection. For example, Zeng et al [78], showed that antibodies against a synthetic epitope of NY-ESO-1 occurred only in 5-10% of the serum samples from patients with different types of cancer. This implicates that in order to exploit antibody responses against tumour antigens for the detection of cancer, a large panel of tumour antigens or epitopes is required to cover a broad range of patients with a particular type of cancer.…”
Section: Early Detection Of Cancermentioning
confidence: 99%
“…Therefore, it is necessary to investigate potential immunogenic epitopes for tumor diagnosis, as demonstrated for cancer/testis Ag NY-ESO-1. Zeng et al (52) identified a 40-aa protein fragment of NY-ESO-1 recognized by autoantibodies in a wide range of patients' sera suffering from different tumor entities. In this study, we determined one TXNDC16 epitope exclusively recognized by autoantibodies in one-third of all tested meningioma sera and one epitope recognized in approximately one-fifth of meningioma sera but also in one control serum.…”
Section: Discussionmentioning
confidence: 99%